Analisis Penerapan Metode Pencatatan Akuntansi Dengan Konsep Accrual Accounting Pada Perbankan Syariah - Robby Gamas; Ersi Sisdianto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The concept of accrual accounting is a basis commonly applied in financial institutions in Indonesia. However, Islamic banks have a different perspective on implementing the accrual accounting concept. This research aims to analyze the application of accounting recording methods with the concept of accrual accounting in sharia banking. The research method is descriptive qualitative research with data collection techniques in the form of library research. The findings show that the implementation of the accrual accounting concept in sharia banking cannot be fully implemented because there are elements that conflict with sharia principles. These elements are uncertainty and gharar, as well as the high potential for institutions to fall into earnings management practices. This makes sharia banking apply a limited accrual method and adapt it to sharia principles. In calculating profit sharing, Islamic banking does not apply accrual accounting because it requires real cash inflows and receipts. Islamic financial institutions can use accrual accounting for financial reports which aims to increase transparency and accountability before stakeholders.